How Folklores Are Utilized As Pedagogical Tools To Instruct Interpreting Students? - Bambang Panca Syahputra; Rakhmat Wahyudin Sagala; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2023)
Interpreting is a much more intricate process than translation. It involves expertise in linguistic and non-linguistic factors, such as cross-cultural comprehension. This article presents the results of a study conducted in a university classroom, specifically focusing on using Folklore in consecutive interpreting activities as a pedagogical tool among interpreting students. This study uses content analysis to explore untranslatable cultural terms in Folklore, particularly in evaluating students' interpreting skills. Moreover, the researchers examine moral lessons and untranslatable terms through student discussions. Students of English Department students participated in this study, chosen based their interpreting assessment. The findings are innovative in that Folklore serves as a pedagogical tool that effectively engages with consecutive interpreting activities by bridging practical experiences with theoretical concepts. This study's findings are novel in that Folklore is a feature of pragmatic teacher-student interaction and a pedagogical tool used to engage with consecutive interpreting students to relate practical experience to theoretical constructs, which spoken language interpreter educators could consider if culturally appropriate. Spoken language interpreter educators should also consider incorporating Folklore as an appropriate cultural approach to enhance the learning experience for their students.